Assessment of batch culture conditions for cyanobacterial propagation for a bioreactor in space - Fahrion, Jana; Dussap, Claude Gilles; Leys, Natalie (Frontiers in Astronomy and Space Sciences, 2023)
One important point in human space exploration is the reliable air, water and food production for the space crew, less dependent from cargo supply. Bioregenerative life support systems aim to overcome this challenge. The life support program MELiSSA of the European Space Agency uses the cyanobacterium Limnospira indica for air revitalization and food production. In the Space flight experiments ArtEMISS-B and -C, Limnospira indica is tested on the International Space Station. In this study we elucidate which conditions are most favorable for cell propagation from inoculum to a full culture in space to enable a high final biomass concentration, with high pigment composition for an efficient bioprocess. We found that lower light intensities (36-75 µmol photons m-2 s-1) show higher maximum biomass densities and higher pigment contents than cultures grown above 100 µmol photons m-2 s-1. 36 µmol photons m-2 s-1 resulted in maximum biomass concentrations of 3.36 ± 0.15 g L-1 (23°C), while cultures grown at 140 µmol photons m-2 s-1 only achieved concentrations of 0.82 ± 0.10 g L-1 (25°C) (-75.8%). Colder temperatures (21-25°C) showed a negative effect on the pigment content. At 36 µmol photons m-2 s-1, a temperature of 30°C gave a phycocyanin concentration of 0.122 ± 0.014 g g DW-1 and 23°C resulted in 0.030 ± 0.003 g g DW-1 (-75.4%). In conclusion, a low light intensity (36-80 µmol photons m-2 s-1) in combination with warm temperature (30-34°C) is optimal to obtain cultures with high pigment contents and high biomass concentrations in a batch culture.